Peculiarities of Teachers’ Coping Strategies - Kepalaitė, Albina (Social Welfare: Interdisciplinary Approach, 2013)
This research aims to reveal teachers’ stress coping peculiarities. It was identifi ed that teachers most often used planful problem solving and accepting responsibility, while escaping-avoidance and confrontation were used most rarely. Female teachers used all coping strategies more often than male teachers. Succession of frequency of coping strategies in male and female groups differs. Senior women use confrontation and distancing coping more rarely than younger women. The specifi city of frequency of coping strategies, considering the delivered subject, was disclosed.